DAMPAK PENGGUNAAN QRIS TERHADAP KEPUASAN KONSUMEN SEBAGAI ALAT TRANSAKASI - Marsanda Aris (2023)
Over time the use of payment instruments has progressed very rapidly. These changes include digital payment instruments which are very helpful and speed up the payment process and help reduce physical contact as a form of reducing the spread of the Covid-19 virus which can be attached to banknotes as a means of payment. Therefore BI issued QRIS, as a style of QRIS payment transaction is the Indonesian Quick Response Code Standard, namely the National QR code standard as a medium for payment of QR codes in Indonesia which was launched by Bank Indonesia. By using payment via QR, the transaction process becomes easier, faster and secure. Using an E-Wallet as a means of payment for several merchants such as LinkAja, Gopay, OVO, DANA, ShopeePay and others is very helpful as a payment transaction tool. Where physical to digital payment instruments become easy, effective and efficient, easy to implement and can be integrated with software that uses the InterActive QRIS Open API Platform. This Final Project is carried out based on a quantitative approach with the causal study writing method, namely writing that is done to state that the independent variables cause or influence the dependent variable. Data collection was carried out through a questionnaire.